(untitled) (Journal of Information Technologies in Education (ITE), 2012)
The article describes basic factors influencing trade policy of Belarus. The factors include Belarus post-soviet specialization and its re-integration strategy with other CIS countries. The article discusses several possible ways of the trade policy development for the small open economy.